Não Khalo: entre as matérias‑fantasma e o Deus Nietzschiano - Raposo, Sílvia (CEM – Cultura, Espaço & Memória, 2020)
This article starts from an art based research on the Não Kahlo performance to evoke the place of Frankensteinian performance as a place of the incorporation of images, questioning and appropriating the concept of hybridity and the Nietzschean theory of the death of God associated with Post‑Modernism and the advent of the ‘end of art’ through its intersection with the concept of mediality in art and the theory of ‘phasma’ in image according to Jean Pierre Vernant. Through Vernant’s theory, which claims an understanding of the image as part equally composed of «pictura» and «imago», the place of the contemporary artist is claimed as double entity that integrates the Superman and the God of Nietzsche, evoking new mediality formats in art, redefining the concept of cinematographic medium from the notion of ‘ghostly‑matters’, in a search for a cinema medium that is not restricted to the film or projected image.